2018
DOI: 10.1016/j.joto.2018.05.005
|View full text |Cite|
|
Sign up to set email alerts
|

Case of Waardenburg Shah syndrome in a family with review of literature

Abstract: Waardenburg syndrome is a rare disease characterized by sensorineural deafness in association with pigmentary defects. Depending on additional symptoms, WS have been classified into four types. Waardenburg syndrome type 4, also called as Waardenburg Shah Syndrome is a very rare congenital disorder with astounding variable clinical expression, characterized by pigmentary abnormalities of the hair (A white forelock of hair, premature graying) and pigmentary changes of the iris such as heterochromia or homochromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Type 3 shows abnormalities of arms and hands in addition to typical features of WS [ 7 ]. Type 4 presents symptoms of both WS and Hirschsprung disease, an intestinal disorder with severe constipation or blockage of the intestine [ 16 ]. In this study, the proband showed WS features with 1.75 W index which was less than 1.95 (The most significant difference between WS type 1 and type 2 is dystopia canthorum.…”
Section: Discussionmentioning
confidence: 99%
“…Type 3 shows abnormalities of arms and hands in addition to typical features of WS [ 7 ]. Type 4 presents symptoms of both WS and Hirschsprung disease, an intestinal disorder with severe constipation or blockage of the intestine [ 16 ]. In this study, the proband showed WS features with 1.75 W index which was less than 1.95 (The most significant difference between WS type 1 and type 2 is dystopia canthorum.…”
Section: Discussionmentioning
confidence: 99%
“…WS can be recognized by some specific clinical features that appear after birth; not all affected individuals possess all the clinical features [2]. It has four clinical subtypes based on the mutant gene and characteristic morphology [10]. These morphological features are broad nasal root, white forelock, the difference in the colour of eyes, congenital leukoderma, and sensorineural deafness [10].…”
Section: Discussionmentioning
confidence: 99%
“…It has four clinical subtypes based on the mutant gene and characteristic morphology [10]. These morphological features are broad nasal root, white forelock, the difference in the colour of eyes, congenital leukoderma, and sensorineural deafness [10]. It is a clinical diagnosis, and Waardenburg consortium proposed diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotype-phenotype correlation between a causative gene mutation and various clinical features in WS are largely unclear. Until recently, mutations in EDN3 (20q13.32), EDNRB (13q22.3), MITF (3p14p13), PAX3 (2q36.1), SNAI2 (8q11.21), and SOX10 (22q13.1) have been reported in isolated patients as well as in families segregating WS [6][7][8]. For an instance, mutations of PAX3 gene is recognized as a key indicator for the clinical features of WS1 and WS3, and mutations in MITF, SOX10, and SNAI2 genes are identified in WS2.…”
Section: Introductionmentioning
confidence: 99%